2007
DOI: 10.1007/s00203-007-0243-8
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Streptomyces coelicolor mutants affected in the proteasome system reveals changes in stress-responsive proteins

Abstract: Prokaryotic 20S proteasomes are confined to archaebacteria and actinomycetes. Bacterial targets of this compartmentalized multi-subunit protease have not yet been identified and its physiological function in prokaryotes remains unknown. In this study, intracellular and extracellular proteomes of Streptomyces coelicolor A3(2) mutants affected in the structural genes of the 20S proteasome, in the gene encoding the presumed proteasome-accessory AAA ATPase ARC, or in two putative proteasome-associated actinomycete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
30
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 89 publications
3
30
0
Order By: Relevance
“…These results are consistent with the phenotypes of mutants of the proteasome associated genes mpa and pafA 19 . Increased resistance to organic peroxide has also been reported for S. coelicolor proteasome mutants and was accompanied by increased levels of haloperoxidase 29 . The mechanisms by which the core proteasome protects Mtb against nitrosative damage may include removal of nitrosylated proteins, as demonstrated in mammalian cells 30 .…”
Section: Discussionmentioning
confidence: 61%
“…These results are consistent with the phenotypes of mutants of the proteasome associated genes mpa and pafA 19 . Increased resistance to organic peroxide has also been reported for S. coelicolor proteasome mutants and was accompanied by increased levels of haloperoxidase 29 . The mechanisms by which the core proteasome protects Mtb against nitrosative damage may include removal of nitrosylated proteins, as demonstrated in mammalian cells 30 .…”
Section: Discussionmentioning
confidence: 61%
“…This substitution obviates the need for the Dop-catalyzed deamidation of Pup (which precedes pupylation in most other bacteria) and thus leaves open questions about the function of the Dop in S. coelicolor. As was the case in M. tuberculosis, it has been reported that the prc genes are not essential for viability (20,21). However, proteomic analyses of the S. coelicolor prc null strain revealed a marked overproduction of proteins that mediate stress responses (21).…”
Section: Importancementioning
confidence: 95%
“…While the relevance of the Pup-proteasome system to the pathogenicity of M. tuberculosis has made it the focus of much attention, we and others (20,21) have been intrigued by the homologous system in Streptomyces bacteria. These actinobacteria are best known as producers of antibiotics and for their complex life cycle, during which both morphological differentiation and sporulation occur (22)(23)(24).…”
Section: Importancementioning
confidence: 99%
“…The targeting of proteins to proteasomes requires the conjugation of a small "Pup" (prokaryotic ubiquitin-like protein) tag to substrates (275). The Streptomyces 20S proteasome was first identified in 1998, and its functions were initially investigated in 2007 (278,282). A different protein profile was noticed in proteasome mutants of S. coelicolor, though no specific proteasome target was identified.…”
Section: Protein Degradation Machinerymentioning
confidence: 99%